The SETscore to predict tracheostomy need in cerebrovascular neurocritical care patients - Schönenberger, Silvia; Al-Suwaidan, Faisal; Kieser, Meinhard; Uhlmann, Lorenz; Bösel, Julian (Neurocritical care, 2016)
Patients with severe stroke who require mechanical ventilation and neurointensive care unit (NICU) management often require a tracheostomy (TT). The optimal time point for TT remains unclear and a controversy in everyday NICU life. Here, we prospectively evaluated a score for prediction of TT need in NICU patients with cerebrovascular disease.
Gesehen am 22.05.2020